The Concept of International Security - Adhikari, Abhaya Shekhar (Hasanuddin Journal of International Affairs, 2024)
To grasp the idea of international security, it is crucial to clarify the broader notion of security. A full understanding of international security can only be attained once the concept of security is comprehended. The shift in the understanding of security from the traditional approach to a more expansive one has created challenges in defining what security truly entails, resulting in it being considered as an essentially contested concept. Nevertheless, it is important not to use this disagreement as an excuse to avoid providing one's own definition. It is imperative to establish one's own conceptualization of security before delving into any work on security. This study formulates a comprehensive conceptualization of security reinstating the special role of state in security affairs that has been shadowed by the expansionist concept. The paper then applies the framework to conceptualize international security taking into consideration the unique complexities associated with the global context.